Synergy of Parents and Madrasas: Building a Violence-Free Generation - Hidayati, Zuhriyyah; Sya'roni, Muhammad; Subhan, Muhammad; Rahmah, Avivah (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
The problem of violence and bullying in the educational environment, especially madrasas, is still a serious challenge that has an impact on the comfort and safety of students. This study aims to examine the effectiveness of synergy between parents and madrassas in preventing violence with a Participatory Action Research (PAR) approach. Through mentoring at MI Qomarul Wathon Lamongan, this research involves problem mapping, the preparation of anti-violence SOPs, education for students and parents, and the implementation of parenting programs as a form of strategic collaboration. The study's results demonstrate that a strong and structured partnership can create a safe learning environment, increase awareness of the dangers of violence, and cultivate an empathetic and moral character in children. These findings confirm that the synergy between parents and madrassas is crucial in building a violence-free generation and can serve as a model for replication in other madrassas.